Labour Productivity Improvement Model - Paudyal, Ramjee Prasad (Tribhuvan University Journal, 2013)
Majority of the share investment in the enterprises are initiated by the Government of Nepal. This study has considered productivity model developed the Sumanth (1984). Accordingly, some of the variables are identified for the productivity improvement like: productivity planning, improvement, measurement, and evaluation. The basic objective of the study is to assess the labour productivity of the manufacturing public enterprises in Nepal. This study reveals that the concept of productivity and its benefits to investors, employees, government, society and the enterprises themselves, were not properly understood and realized by the employees of the enterprises. The managers were also doubtful about the effectiveness of the existing personnel policies. The major problems associated with productivity improvement were found to be underutilization of production capacity and poor maintenance of machines. Similarly socio-cultural contexts like favoritism, nepotism, and corruption had seriously influenced the appraisal practices, and the productivity status. The productivity was also suffered because of the failure of the management to adjust to the changes taking place within the workforce. In managing human resources, leadership styles and motivational systems had not kept abreast of these changes.